2019
DOI: 10.1002/jmri.26884
|View full text |Cite
|
Sign up to set email alerts
|

Histogram analysis of diffusion kurtosis imaging based on whole‐volume images of breast lesions

Abstract: Background Breast diffusion kurtosis imaging (DKI) is a novel MRI technique to assess breast cancer but the effectivity still remains to be improved. Purpose To investigate the performance of whole‐volume histogram parameters derived from a DKI model for differentiating benign and malignant breast lesions. Study Type Retrospective. Population In all, 120 patients with breast lesions (62 malignant, 58 benign). Sequence DKI sequence with seven b‐values (0, 500, 1000, 1500, 2000, 2500, and 3000 s/mm2) and DWI seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…In a previous study, Iima et al (36) used non-Gaussian diffusion and IVIM-DWI to diagnose breast lesions and found that the AUC of ADC0 was significantly higher than that of MK, suggesting the superiority of conventional DWI and it having more clinical availability. A complex and heterogeneous microstructure is a common feature of malignant tumors arising from necrosis, cancer nests, intraductal components, and plenty of barriers and compartmentalization between or within the cells (18). The diffusion of water molecules in this microenvironment will deviate from the mono-exponential Gaussian model at high b-values, leading to inaccurate fitting and calculation of the diffusion coefficient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, Iima et al (36) used non-Gaussian diffusion and IVIM-DWI to diagnose breast lesions and found that the AUC of ADC0 was significantly higher than that of MK, suggesting the superiority of conventional DWI and it having more clinical availability. A complex and heterogeneous microstructure is a common feature of malignant tumors arising from necrosis, cancer nests, intraductal components, and plenty of barriers and compartmentalization between or within the cells (18). The diffusion of water molecules in this microenvironment will deviate from the mono-exponential Gaussian model at high b-values, leading to inaccurate fitting and calculation of the diffusion coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…Jensen et al (11) first introduced the DKI model in 2005 and developed new fields in brain, liver, and prostate imaging afterward (12)(13)(14). The investigation of breast tumors using the DKI model reached a peak in 2019 and became an important research area thereafter (8,(15)(16)(17)(18)(19)(20). The model provides microscopic information regarding the deviation of water diffusion from Gaussian distribution with the mean kurtosis (MK) and mean diffusivity (MD), a kurtosiscorrected diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, the study investigated the widely used DWI technique using 2 b-values. However, more advanced MRI sequences, such as intravoxel incoherent motion and diffusion kurtosis imaging might show a better accuracy in discriminating BC phenotypes [57,58]. Yet, there are few studies using these sequences and thus no comprehensive analysis can be made.…”
Section: Discussionmentioning
confidence: 99%
“…The number of malignant and benign lesions ranged from 14-259 and 8-161, respectively, with a mean of 61 malignant and 36 benign lesions per study subset. Seven study subsets were categorized as BTTS1: whole breast tumor tissue selection [35,[38][39][40][41][42][43], 22 as BTTS2: subtracted whole breast tumor tissue selection [15][16][17]20,23,36,37,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], 19 as BTTS3: circular breast tumor tissue selection [18,19,21,24,25,36,[59][60][61][62][63][64][65][66][67][68][69][70][71] and 17 as BTTS4: lowest diffusion breast tumor tissue selection…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%